Detection of small for gestational age babies and perinatal outcomes following implementation of the Growth Assessment Protocol at a New Zealand tertiary facility: An observational intervention study. (19th December 2020) - Cowan, F. Joyce; McKinlay, Christopher J. D.; Taylor, Rennae S.; Wilson, Jess; McAra‐Couper, Judith; Garrett, Nick; O'Brien, Andrea; McCowan, Lesley M. E.
Abstract : Background: Timely detection of small for gestational age (SGA) fetuses is important for reducing severe perinatal morbidity and mortality, and better tools are needed to detect SGA in maternity care. Aim: We evaluated the effect of the introduction of the Perinatal Institute's Growth Assessment Protocol (GAP) in the Counties Manukau Health region, South Auckland, New Zealand, on antenatal detection of SGA and maternal and perinatal outcomes. Materials and Methods: Uncontrolled before and after study in women booked under hospital community midwife care with a singleton, non‐anomalous pregnancy. Antenatal detection of SGA (birthweight <10th customised centile) was compared pre‐GAP (2012, N = 1105) and post‐GAP (2017, N = 1082). Composite adverse neonatal outcome was defined as neonatal unit admission >48 h, five‐minute Apgar score <7, and/or any ventilation. Analyses were adjusted for maternal age, body mass index, deprivation, smoking and ethnicity. Results: SGA rates were similar across epochs (13.8% vs 12.9%) but antenatal detection of SGA increased from 22.9% (35/153) to 57.9% (81/140) post‐GAP (adjusted odds ratio (aOR) = 4.8, 95% CI 2.82–8.18). Rates of induction of labour and caesarean section increased between epochs but were similar in SGA, non‐SGA, and detected and non‐detected SGA subgroups. Among SGA babies, there was some evidence that antenatal detection of SGA may be associated with lower composite adverse neonatal outcome (detected SGA: aOR 0.44 95% CI 0.17–1.15; non‐detected SGA: aOR = 1.81 95% CI 0.73–4.48; interaction P = 0.03). Pre‐term birth did not appear to be influenced by GAP. Conclusion: Implementation of GAP was associated with a nearly five‐fold increase in SGA detection without increasing obstetric intervention for SGA.